2018
DOI: 10.1016/j.molp.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoid UDP-Glycosyltransferases from Chinese Sweet Tea and Ashitaba Complete the Biosynthesis of Rubusoside

Abstract: Diterpenoids are important molecules that play significant roles in many biological processes. In plants, acyclic diterpene phytol is a representative side chain of chlorophyll, and tetracyclic diterpene gibberellins ubiquitously serve as plant hormones regulating growth and development. Decoration of diterpene core structures by oxidation and glycosylation are usually key steps to confer final bioactivity of diterpenoid compounds. In contrast to the extensively studied oxidases involved in gibberellin biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…f). Many UGTs catalyse the glycosylation of substrates with similar structures (Lim et al , ; Torrens‐Spence et al , ; Sun et al , ). UGT1 in this study may not be the only UGT to produce phenyllactylglucose from phenyllactate, as other uncharacterized A. belladonna UGTs may also produce phenyllactylglucose in a small amount for littorine biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…f). Many UGTs catalyse the glycosylation of substrates with similar structures (Lim et al , ; Torrens‐Spence et al , ; Sun et al , ). UGT1 in this study may not be the only UGT to produce phenyllactylglucose from phenyllactate, as other uncharacterized A. belladonna UGTs may also produce phenyllactylglucose in a small amount for littorine biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the amino acids in the Nterminal region of UGTs contribute to the regio-specificity of sugar acceptors and that the PSPG box in the C-terminal region of UGTs plays a key role in sugar-donor binding 43,44 . The metabolomics data described above showed that levels of kaempferol, naringenin, quercetin and monolignols were higher in NIL-GSA1 CG14 than in NIL-GSA1 WYJ , whereas the levels of naringenin-7-O-glucoside, quercetin-7-O-glucoside and lignin were significantly lower.…”
Section: Nil-gsa1 Cg14mentioning
confidence: 99%
“…Phenylpropanoid homeostasis among different branches of phenylpropanoid metabolism, which is achieved via the regulation of metabolic flux redirection (MFR), exhibits extraordinary complexity and high‐level plasticity during successive developmental stages and in response to environmental stimuli and changes (Lanot et al, 2008). In the last few decades, a considerable number of studies have unraveled the sophisticated mechanisms that control the biosynthesis of phenylpropanoid metabolites and the regulation of the phenylpropanoid pathway at multiple levels (Figure 1); these studies have led to a comprehensive understanding of phenylpropanoid metabolism and provide the theoretical basis for the genetic improvement of plants and de novo artificial production of metabolites that are beneficial for human health and that meet the demands for horticulture, industry, and agriculture (Lau and Sattely, 2015; Liu et al, 2018; Sun et al, 2018b; Chanoca et al, 2019; Halpin, 2019).…”
Section: Introductionmentioning
confidence: 99%